Хірургічне лікування ізольованих вогнепальних осколкових поранень м’яких тканин шляхом поєднання первинно відтермінованих швів з ін’єкціями в рану збагаченої тромбоцитами аутоплазми при мінно-вибуховій травмі - Завгородній, Сергій Миколайович; Котенко, О. І.; Данилюк, Михайло Богданович; Кубрак, Михайло Анатолійович; Zavhorodnii, S. M.; Kotenko, O. I.; Danyliuk, M. B.; Kubrak, M. A. (Запорізький державний медико-фармацевтичний університет, 2023)
Мета роботи – оцінити ефективність лікування пацієнтів з ізольованими вогнепальними осколковими пораненнями м’яких тканин шляхом накладання первинно відтермінованих швів у комбінації з ін’єкціями в рану збагаченої тромбоцитами аутоплазми при мінно-вибуховій травмі. Матеріали та методи. У дослідження залучили 60 пацієнтів із вогнепальними осколковими пораненнями м’яких тканин. Поранених поділили на дві групи: група порівняння – 30 (50,0 %) пацієнтів, які надійшли в стаціонар із накладеними первинно відтермінованими швами (6–7 доба); основна – 30 (50,0 %) поранених, модифікація місцевого лікування яких полягала в комбінації накладання первинно відтермінованих швів із введенням збагаченої тромбоцитами аутоплазми в рану. Перебіг ранового процесу в рані під швами оцінювали на 8, 11–14 добу від моменту поранення за допомогою візуального огляду, лінійного вимірювання та діагностичної ультразвукової системи (Mindray M6, 220А). Результати. В ургентному порядку на третій етап медичної евакуації госпіталізовані та 60 (100,0 %) пацієнтів, проліковані згідно зі стандартними протоколами лікування цієї патології на третьому етапі евакуації. Структура групи порівняння (n = 30, 50,00 %) за локалізацією ранового дефекту: поранення нижніх кінцівок – у 22 (73,33 %) пацієнтів, верхніх кінцівок – у 6 (20,00 %), тулуба – у 2 (6,67 %). В основній групі – поранені (n = 30, 50,00 %), лікування яких на третьому етапі медичної евакуації модифіковано з використанням комбінації первинно відтермінованих швів та ін’єкції збагаченої тромбоцитами аутоплазми. На 8 добу від моменту поранення під час візуального огляду ран в обох групах не виявили гіперемію та нагноєння рани. Протягом візуального огляду рани на 11,0 ± 3,9 доби від моменту поранення в групі порівняння виявили ускладнення в 24 (80,00 %) випадках: сероми формувались у 17 (56,67 %), гематоми з нагноєнням рани – у 7 (23,33 %). В основній групі зафіксували 2 (6,67 %) випадки нагноєння рани (U = 120,00, р = 0,000001). Aim: to assess the treatment effectiveness in patients with soft tissue gunshot shrapnel injuries by applying primary delayed sutures in combination with platelet-rich autoplasma injections into wounds. Materials and methods. The study included 60 (100.0 %) patients with soft tissue gunshot shrapnel wounds. All wounded were divided into two groups. The comparison group consisted of 30 (50.0 %) patients admitted to a hospital with primary delayed sutures (6–7 days). The main group included 30 (50.0 %) patients whose local treatment modification consisted in a combination of primary delayed suturing with platelet-rich autoplasma injection into a wound. A wound channel was observed on the 8th, 11th –14th days from the moment of injury using visual inspection, linear measurements and diagnostic ultrasound system (Mindray M6, 220A). Results. 60 (100.0 %) patients were urgently hospitalized to the third stage of medical evacuation and treated according to standard treatment protocols for this pathology at the third stage of evacuation. According to a wound defect localization, the wounded of the comparison groups, 30 (50.00 %), were distributed as follows: a lower limb wound – 22 (73.33 %) patients, an upper limb wound – 6 (20.00 %), and a trunk wound – 2 (6.67 %). The main group also included 30 (50.00 %) wounded, whose treatment at the third stage of medical evacuation was modified by using a combination of primary delayed sutures and platelet-rich autoplasma injection. On the 8th day after an injury, a visual inspection of the wounds detected no hyperemia or suppuration in both groups. The visual inspection of wounds in the comparison group at 11.0 ± 3.9 days post-injury revealed 24 (80.00 %) patients with complications such as seromas in 17 (56.67 %) cases, hematomas with wound suppuration – in 7 (23.33 %). In the main group, 2 (6.67 %) cases of wound suppuration were detected (U = 120.00, p = 0.000001). The basic parameters of wound linear measurements according to the diagnostic ultrasound system data at the 11th–14th day post-injury after primary and delayed suturing in the studied groups: in the comparison group, upper limb wounds – S (mm2) 43.3 ± 12.6, V (mm3) 53.3 ± 13.9; lower limb wounds – S (mm2) 194.7 ± 50.7, V (mm3) 706.3 ± 190.4; trunk wounds – S (mm2) 20.5 ± 7.2, V (mm3) 22.5 ± 5.4. In the main group, upper limb wounds – S (mm2) 28.2 ± 8.5, V (mm3) 23.2 ± 7.1; lower limb wounds – S (mm2) 56.4 ± 19.6, V (mm3) 102.4 ± 21.1; trunk wounds – S (mm2) 12.3 ± 3.2, V (mm3) 10.4 ± 2.9. The total duration of inpatient treatment at the 3rd stage of medical evacuation in the comparison group wounded was 30.0 ± 2.3 days, and in the main group it was 12.0 ± 3.1 days (U = 290.00, p = 0.0354).
Surgical treatment of isolated soft tissue gunshot shrapnel injuries by combining primary delayed sutures with platelet-rich autoplasma injections into mine-explosive wounds
Завгородній С. М. - ORCID ID: 0000-0003-3082-3406; Котенко О. І. - ORCID ID: 0000-0002-0253-5610; Данилюк М. Б. - ORCID ID: 0000-0003-4515-7522; Кубрак М. А. - ORCID ID: 0000-0003-4051-9336.
Keywords: вогнепальні осколкові поранення; хірургічне лікування; збагачена тромбоцитами аутоплазма; первинно відтерміновані шви; мінно-вибухова травма; isolated gunshot shrapnel injuries; combined surgical treatment; plateletrich autoplasma; primary delayed sutures; mineexplosive trauma